Strategic Targeting of Plasmodium Dihydroorotate Dehydrogenase through Antimicrobial Artemisinin Chiral Centers and their Derivatives: An Integrative Study Using Network Pharmacology and Isothermal Titration Calorimetry - Rehman, Zia ur (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Developing effective antimalarial medications requires understanding the interactions between Plasmodium Dihydroorotate dehydrogenase (DHOdehase) and Artemisinin, including its fourteen stereoisomers (R/S) which have distinct pharmacological effects due to seven chiral centres. Materials and Methods: Computational techniques, including molecular docking and network pharmacology, were used to generate and analyse Artemisinin’s stereoisomers. The binding strength and durability of the interactions between the stereoisomers and DHOdehase were examined. STRING DB network analysis and pathway enrichment analysis were conducted to identify functional partners and biological pathways associated with DHOdehase. Results: The study identified C6 and C8 positions of Artemisinin’s stereoisomers as potential binding sites with DHOdehase, showing negative binding energies of -8.7 and -8.2 kcal/mol, respectively. The ligand-protein interactions included hydrogen bonds, Van der Waals forces, Pi-Sigma, alkyl/Pi-alkyl and carbon-hydrogen bonds. STRING DB network analysis revealed DHOdehase interactions with 10 functional partner proteins with confidence scores between 0.889 and 0.999. Pathway enrichment analysis linked DHOdehase to pyrimidine metabolism (KEGG term map00240). Additionally, Isothermal Titration Calorimetry (ITC) demonstrated higher affinity parameters for Artemisinin and its stereoisomer Artesunate. Conclusion: The molecular docking, ITC results and network analysis provide insights into the interaction and pharmacological profiles of Artemisinin stereoisomers, laying the groundwork for experimental validation and the development of more effective antimalarial treatments.
Keywords: Malarial Parasite; Plasmodium species; Artemisia annua; Artemisinin; Dihydroorotate dehydrogenase; Molecular docking; Network Biology